CCD Image Sensors in Deep-Ultraviolet Degradation Behavior and Damage Mechanisms - Li, Flora M.; Nathan, Arokia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
As the deep-ultraviolet (DUV) laser technology continues to mature, an increasing number of industrial and manufacturing applications are emerging. For example, the new generation of semiconductor inspection systems is being pushed to image at increasingly shorter DUV wavelengths to facilitate inspection of deep sub-micron features in integrated circuits. DUV-sensitive charge-coupled device (CCD) cameras are in demand for these applications. Although CCD cameras that are responsive at DUV wavelengths are now available, their long-term stability is still a major concern. This book describes the degradation mechanisms and long-term performance of CCDs in the DUV, along with new results of device performance at these wavelengths.
Overview of CCD -- CCD Imaging in the Ultraviolet (UV) Regime -- Silicon -- Silicon Dioxide -- Si-SiO2 Interface -- General Effects of Radiation -- Effects of Radiation on CCDs -- UV-Induced Effects in Si -- UV Laser Induced Effects in SiO2 -- UV Laser Induced Effects at the Si-SiO2 Interface -- CCD Measurements at 157nm -- Design Optimizations for Future Research -- Concluding Remarks.
Keywords: Materials science; Optics; Optoelectronics; Plasmons (Physics).; Engineering; Electronics; Microelectronics; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Optics, Optoelectronics, Plasmonics and Optical Devices; Engineering, general; Electronics and Microelectronics, Instrumentation; Electronic books